Bilayer membrane liposome mimicking red blood cell for drug delivery applications / Sumaira Naeem - Sumaira , Naeem (2019)
The advancement of research in colloidal systems has led to the increased application of this technology in more effective and targeted drug delivery. The first closed bilayer phospholipid system, the liposome system, has been making steady progress in achieving many desirable parameters such as drug loading, size-controlling measures, stability longer circulation half-lives, triggered release and in overcoming obstacles to cellular and tissue uptake of drugs with improved biodistribution in vitro and in vivo. The current study focused on preparing liposomes which could mimic certain characteristics of red blood cell bilayer membranes to overcome problems in sustained and targeted drug delivery. With this aim, liposomes from different phospholipids namely L-α-Phosphatidylcholine (PC), 1,2-Dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) , 1,2-Distearoyl-sn-glycero-3-phosphocholine (DSPC), 1,2-Diacyl-sn-glycero-3-phospho-L-serine (PS) and L-α-Phosphatidylinositol (PI) were formulated in combination with surfactants Polysorbate 80 (TWEEN® 80) and dihexadecyl phosphate (DCP) under physiological conditions. Phosphatidylinositol and dicetyl phosphate were expected to enhance the negative zeta potential of the liposomes in order to mimic red blood cell zeta potential. The newly prepared liposomes were formulated for efficient anticancer drug delivery applications. Liposomes were prepared from thin film hydration technique followed by sonication. Under the optimal experimental conditions, liposomes were formulated to mimic red blood cell surface charge (-3 mV to -14 mV) with a particle size range of 70 nm to 80 nm. The stability of all formulations was investigated by their mean particle size and zeta potential at 4 °C, 28 °C, and 37 °C for 28 days. The presence of liposomes in unsonicated formulations was identified by an optical polarizing microscope which was followed by transmission electron microscopy and field emission scanning electron microscopy for identification of sonicated liposomes. Encapsulation efficiency for all liposomes loaded with different anticancer drugs was more than 60 % using viva spin centrifugal units, however, anticancer drugs with intermediate log P were encapsulated more than 60 %. Less than 20 % of the anticancer drugs were released in first 12 hours showing a released property very useful for inhibiting the proliferation of cancer cells. MDA-MB-231 breast cancer cell line was selected to investigate the in vitro cytotoxic effects of selected liposomes with most commonly used anticancer drug DOX (F1-DOX, F2-DOX, F3-DOX as model formulations) and their response to free and encapsulated DOX concentrations. These liposomes were found to induce significant suppression in MDA-MB-231 breast cancer cell growth qualitatively, whereas no cytotoxicity was observed due to unloaded F3-Liposomes. An obvious cell uptake of DOX was observed by its fluorescence property. Cell uptake by flow cytometry though was quantitatively less than free drug, yet these newly formulated DOX-loaded targeted F3-liposomes suggest potential utility as anticancer agents and may be beneficial for manufacturing biomimetic systems for drug delivery applications.